2019
DOI: 10.1038/s41598-019-52348-6
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal activation related to spontaneous creativity with rock music improvisation: A functional near-infrared spectroscopy study

Abstract: Understanding how the brain modulates improvisation has been the focus of numerous studies in recent years. Models have suggested regulation of activity between default mode and executive control networks play a role in improvisational execution. Several studies comparing formulaic to improvised sequences support this framework and document increases in activity in medial frontal lobe with decreased activity in the dorsolateral prefrontal cortex (DLPFC). These patterns can be influenced through training and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 46 publications
3
30
1
Order By: Relevance
“…The left and right dorsolateral prefrontal cortex (DLPFC) is bilaterally active when performing creativity tasks that require new associations and evaluations (Funahashi 2017). For instance, activation in the left DLPFC decreases (Tachibana et al 2019) and activation increases in the right DLPFC during improvization (De Dreu et al 2012;Kleibeuker et al 2013). The medial PFC (mPFC) and ventrolateral PFC (VLPFC), are also involved in creative design tasks.…”
Section: Cognitive Functions In the Prefrontal Cortex (Pfc) Relating mentioning
confidence: 99%
“…The left and right dorsolateral prefrontal cortex (DLPFC) is bilaterally active when performing creativity tasks that require new associations and evaluations (Funahashi 2017). For instance, activation in the left DLPFC decreases (Tachibana et al 2019) and activation increases in the right DLPFC during improvization (De Dreu et al 2012;Kleibeuker et al 2013). The medial PFC (mPFC) and ventrolateral PFC (VLPFC), are also involved in creative design tasks.…”
Section: Cognitive Functions In the Prefrontal Cortex (Pfc) Relating mentioning
confidence: 99%
“…Music that evokes strong emotional valence is associated with altered activity not only in the superior temporal gyrus but also in the caudate nucleus, insula, thalamus, cingulate cortex, orbitofrontal, dorsomedial, dorsolateral and ventromedial prefrontal cortex, inferior frontal cortex and supplementary motor area (e.g., Blood and Zatorre, 2001 ; Koelsch et al, 2006 ; Mitterschiffthaler et al, 2007 ; Chapin et al, 2010 ; Brattico et al, 2011 ; Pereira et al, 2011 ; Khant et al, 2012 ; Altenmüller et al, 2014 ; Koelsch, 2018 ; Särkämö and Sihvonen, 2018 ; Sachs et al, 2019 ). Of course, music involves more than just listening, and imaging of people—alone or with others—creating and improvising jazz, rap or rock music has also revealed increased neural activity in the medial frontal lobe and altered, usually decreased, activity in the dorsolateral prefrontal cortex when compared to the same subjects playing or singing “formulaic sequences” (Limb and Braun, 2008 ; Liu et al, 2012 ; Donnay et al, 2014 ; Tachibana et al, 2019 ).…”
Section: The Links Between Oxytocin and Musicmentioning
confidence: 99%
“…The nature of the musical activity is important because an increase in plasma oxytocin levels in members of a vocal jazz group was only recorded when singers were improvising together (Keeler et al, 2015 ), likely due to altered activity in the prefrontal cortex and enhanced affiliative and prosocial interactions (Limb and Braun, 2008 ; Liu et al, 2012 ; Donnay et al, 2014 ; Tachibana et al, 2019 ). Schladt et al ( 2017 ) reported that salivary oxytocin levels slightly increased when subjects were solo singing but were decreased when singing in a choir.…”
Section: The Links Between Oxytocin and Musicmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the literature consistently demonstrates an interplay of the default mode network (DMN) and executive control network during tasks that involve creative improvisation ( Boccia et al. , 2015 ; Tachibana et al. , 2019 ; Chen et al.…”
Section: Introductionmentioning
confidence: 99%